Korelasi Tingkat Kepatuhan Konsumsi Obat Antiepilepsi Menggunakan Kuesioner MGLS (Morisky, Green, Levine Adherence Scale) dengan Frekwensi Kejang Pasien Epilepsi - Ernawati, Iin; Islamiyah, Wardah Rahmatul (Jurnal Farmasi Udayana, 2021)
Epilepsy is a chronic non-communicable brain disorder that can affect people of all ages. AED (antiepileptic drug) is the main therapy for most epilepsy patients with the overall goal being to prevent seizures without causing side effects. One measure of management of drug therapy in epilepsy is the decrease / loss of seizures, so that the frequency of seizures is one of the measures to achieve end-outcome. This study was an observational cross sectional study conducted on outpatients in Airlangga University Hospital, which aims to look at the relationship between the level of adherence using antiepileptic drugs with the incidence of seizures in epilepsy patients. The level of adherence with AED consumption in this study used the MGLS questionnaire (Morisky, Green, Levine Adherence Scale). The level of adherence based on the MGLS questionnaire was divided into 3 levels including low, medium or medium obedient and high compliant. The seizure events in epilepsy patients observed were the presence or absence of seizures during the past month, the data of which were obtained from patient or family interviews and from diary seizures. The results of the study of 40 respondents found that there was a moderate positive correlation between the level of adherence measured using the MGLS questionnaire whose majority level of adherence was moderate with the occurrence of seizures in epilepsy patients (r = 0.423 with p = 0.006 <0.05.